Is IEEE 802.11 ready for VoIP? - Conceicao, Arlindo F.; Li, Jin; Florencio, Dinei; Kon, Fabio (Institute of Electrical and Electronics Engineers, Inc., 2006)
In this paper, we empirically explore voice communication over IEEE 802.11 networks (VoWiFi). The objective is to understand the limitations of the current WiFi network for VoWiFi deployment. Our experiment finds two major problems of VoWiFi: unstable and excessively long handoffs and unpredictable occurrence of bursts. We also discuss several other minor factors that could hinder VoWiFi deployment, such as network capacity, fairness, and interference susceptibility. Finally, we describe the scenarios where VoWiFi could be used. We conclude that VoWiFi is feasible if used moderately, with low mobility and good signal strength.